PERUBAHAN SIFAT KIMIA BUAH AVOKAD PADA BEBERAPA SUHU PENYIMPANAN - UTAMI, N.W; SUTARNO, H.; CITROREKSOKO, P.S. (BERITA BIOLOGI, 1986)
N.W UTAMI, H.SUTARNO&P.S.CITROREKSOKO.1986.Changes of chemical constituents of avocado fruits as affected by various storage temperatures.Berita Biologi 3(4) 163-166.Effects of storage temperatures on avocado fruits were observed in laboratoty at 25 °C,28± 1°C and 33°C for 0,4,7 and 12 days,Results of these experiment were intended to know the best quality of the fruits during the storage period.The results indicated that the best quality of the fruits was stored at 31 °C for 7 days.The biochemical content such as carotenoid was 1198.31 1.U.vitamin A,Whereas the oil content was 12.07% and the decomposition of the oil ws very slow